Franny, the queen of Provincetown - Preston, John. (Vancouver Arsenal Pulp Press, 2005)
First published to wide acclaim in 1983, Franny was a book of gay heroism and camaraderie in the shadow of the burgeoning AIDS crisis. Today, one can read it with a sense of nostalgia, and with the knowledge that Franny's dream of a society that accepts gays and lesbians without question is closer to fruition, but far from complete.
Introduction by Michael Lowenthal -- Franny, the Queen of Provincetown -- Appendices : -- "Queens rule" by John W. Rowberry -- Interview with John Preston by Philip Gambone -- "Preston on publishing : building libraries ... with help from mom" by John Preston -- "Drag queens, leathermen, and telling the truth" by Dusk Peterson -- Excerpt from John Preston's C.V., 1993 -- "Franny in New York" by T.R. Witomski -- Cover art of the original Alyson edition.
First published: Boston : Alyson, 1983.
Keywords: Gay men -- Fiction; Friendship -- Fiction; Provincetown (Mass.) -- Fiction